Advancing topical drug delivery: NLC innovations in dermatological therepeutics - Balaji; Prakash Goudanavar (Nano Trends)
Nanostructured lipid carriers (NLCs) are promising drug delivery systems with broad therapeutic applications. This review covers recent advancements, challenges, and future prospects in NLC-based drug delivery. It introduces the rationale and benefits of NLC use, discussing formulation strategies like high-pressure homogenization, solvent emulsification-evaporation, and micro emulsion techniques. Unique properties, such as enhanced drug loading, controlled release, and improved stability, are highlighted. The application of NLCs in targeted drug delivery is explored, addressing challenges like low solubility, poor bioavailability, and systemic toxicity. Development challenges, including scalability, characterization, and regulatory approval, are discussed, along with potential solutions. Recent advancements like surface modification, co-delivery systems, and engineered NLCs for targeted therapy are elucidated. NLCs in topical drug delivery, particularly in dermatology, are examined for treating skin conditions with minimal systemic effects. Future directions and trends, including personalized medicine and theranostic integration, are discussed, emphasizing NLCs' potential across diverse medical applications. This review provides insights into NLC-based drug delivery's current state, emphasizing their role in advancing therapeutic outcomes.